Observational Needs for Improving Ocean and Coupled Reanalysis, S2S Prediction, and Decadal Prediction - Penny, Stephen G.; Akella, Santha; Balmaseda, Magdalena A.; Browne, Philip; Carton, James A.; Chevallier, Matthieu; Counillon, Francois; Domingues, Catia; Frolov, Sergey; Heimbach, Patrick; Hogan, Patrick; Hoteit, Ibrahim; et al. (Frontiers in Marine Science, 2019)
Developments in observing system technologies ocean data assimilation (DA) and are symbiotic. New observation types lead to new DA methods, and new DA methods such as Coupled Data Assimilation can change the value of existing observations or indicate where new observations can have greater utility for monitoring and prediction. Practitioners of DA are encouraged to make better use of observations that are already available, for example taking advantage of strongly coupled data assimilation so that ocean observations can be used to improve atmospheric analyses and vice versa. Ocean reanalyses are useful for the analysis of climate, as well as initializing operational long-range prediction models. There are remaining challenges for ocean reanalyses due to biases and abrupt changes in the ocean observing system throughout its history, the presence of biases and drifts in models, and simplifying assumptions made in DA solution methods. From a governance point of view, more support is needed to bring the ocean observing and DA communities together. For prediction applications, there is wide agreement that protocols are needed for rapid communication of ocean observing data on numerical weather prediction (NWP) timescales. There is potential for new observation types to enhance the observing system by supporting prediction on multiple timescales, ranging from the typical timescale of NWP covering hours to weeks, out to multiple decades. It is encouraged that greater communication be fostered to allow operational prediction centers the ability to provide guidance for the design of a sustained and adaptive observing network.